Estudos dos marcadores temporais na leitura em língua estrangeira - Jeronimo Coura Sobrinho (2004)
In this study the interpretations of the linguistic manifestations of time and its relations with aspect and modality are discussed. Eighty undergraduate Brazilian students of the technological area, who were enrolled in a reading course in English as a Foreign Language, were the research subjects. The data were collected during the final term examination. A task specially designed to achieve both the purposes of the evaluation and research was carried out in the classroom, after the reading of four authentic texts of the same genre, which were of interest for the students. In this exploratory research, effort was made to keep the natural classroom environment unchanged during data gathering, leaving both the teacher and the students in their roles. Data revealed a considerable difference in the interpretations of the utterance production frame, i.e., the distinction made by the French tradition of the works ofÉmile BENVENIST between discourse and history. The research subjects were not able to perceive the different meanings of some absolute tenses neither did they understand the temporal dimension of verbal modalities. The variability of the interpretations of the categories of time suggests that the temporal dimension of discourse is an important component of reading comprehension and that temporality should be considered as a relevant element in reading courses in foreign language